Canberra red : stories from the bush capital - Headon, David John, 1950-; MacKenzie, Andrew (Allen & Unwin, 2013)
From the humble red brick houses scattered around the lake to the grand monuments designed to reflect the aspirations of a new nation, it is one of the great planned cities of the world. This collection explores the stories of the people and institutions of Canberra, and reflects on what has become of the great vision of Walter Burley Griffin a century on.